Eﬀects of task-speciﬁc training on motor activity, cognitive function, and quality of life among individuals with Parkinson’s disease: a quasi-experimental pilot study - Suganthirababu, Prathap; Srinivasan, Vignesh; Abathsagayam, Kumaresan; Vishnuram, Surya; Parthiban K. (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. The second most prevalent neurological condition in adults over 50 years is Parkinson’s disease (PD). Individu-als with PD(IwPD) experience motor and non-motor symptoms during disease progression. One of the most signiﬁcant vari-ables in non-motor symptoms is cognitive impairment, andthe disease may lead to dementia. Even though the cognitive impair-ment in IwPD is mild, there should be concern regarding its rehabilitation because there is no pharmacological management for cognitive impairment, and just a handful of studies on functional cognitive training for IwPD have been published. This raises the prospect of task-speciﬁc training among IwPD and functional rehabilitation of cognitive function.Methods. Thisquasi-experimental study involved 30 participants, who were assessed and selected based on inclusion and exclu-sion criteria. Pre-test and post-test values were obtained using the Montreal Cognitive Assessment (MoCA), Uniﬁed Parkinson’s Disease Rating Scale (UPDRS) Part III, and Parkinson’s Disease Questionnaire (PDQ)-39. All subjects underwent task-speciﬁc training with cognitive training for 8 weeks.Results. Statistical analysisshowed signiﬁcant improvements in motor activity, cognitive function, and quality of life. The p-value of each outcome measure was < 0.0001 after analysingpre-test and post-test data.Conclusions. According to the ﬁndings ofthis study, task-speciﬁc training combined with cognitive training signiﬁcantly improved motor activity, cognitive function, and quality of life among IwPD.
Keywords: cognition; Parkinson’s disease; dementia; non-motor symptom; functional mobility; quality of life